Superhydrophilic multifunctional nanotextured titanium dental implants: in vivo short and long-term response in a porcine model. (22nd December 2021) - Mathew, Anil; Abraham, Silpa; Stephen, Shamilin; Babu, Anna Serene; Gowd, Siddaramana G.; Vinod, Vivek; Biswas, Raja; Nair, Manitha B.; Unni, A. K. K.; Menon, Deepthy
Abstract : Titanium dental implants with nano or micro-nano topographies generated by hydrothermal treatment are superhydrophilic and demonstrate multifunctional activity in vivo . Abstract : Current clinical demand in dental implantology is for a multifunctional device with optimum mechanical properties, improved biocompatibility and bioactivity, and having differential interactions with cells and pathogenic agents. This would minimise bacterial infection, biofilm formation and modulate inflammation, leading to a fast and durable osseointegration. The present study intends to establish the multifunctional behaviour of surface modified titanium dental implants that are superhydrophilic, with unique micro-nano or nanoscale topographies, developed by a facile hydrothermal technique. Here, the short and long-term performances of these textured implants are tested in a split mouth design using a porcine model, in pre- and post-loaded states. Quantitative and qualitative analyses of the bone implant interphase are performed through μ-CT and histology. Parameters that evaluate bone mineral density, bone contact volume and bone implant contact reveal enhanced bone apposition with better long-term response for the nano and micro-nano textured surfaces, compared to the commercial microtextured implant. Concurrently, the nanoscale surface features on implants reduced bacterial attachment by nearly 90% in vivo, outperforming the commercial variant. This preclinical evaluation data thus reveal the superiority of nano/micro-nano textured designs for clinical application and substantiate their improved osseointegration and reduced bacterial adhesion, thus proposing a novel dental implant with multifunctional characteristics.